Nilai Pendidikan Karakter Religius dan Sains dalam Film Animasi “Riko The Series” Sebagai Media Pembentuk Pengetahuan dan Karakter Religius - Muna, Naili Wirdatul; Solehuddin, Sugeng; Mahmudah, Umi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
This study aims to determine the value of religious and scientific character education in the Riko The series film and how the animated film Riko The series can shape the knowledge and religious character of elementary school children. The type of research used in this study is a literature review. The approach used is a qualitative approach. The primary data source in this study is 10 episodes of the Riko The series animated film. The secondary data source in this study is documents or books that are able to explain the purpose of the study. The analysis used is a semiotic mode analysis. The value of religious character education in the Riko The series animated film includes: Faith, patience, Al ukwah, Religion, Knowledge, Gratitude, and Tawadhu'. The sciences contained in the Riko The series animated film include: Geology, Biology, Astronomy, and Physics. From the results of reviewing several theories and values ​​of character education and science contained in the animated film Riko The series, the author concludes that the animated film Riko The series can be used as a media for forming knowledge because it is in accordance with the cognitive growth stage of elementary school children who are at the concrete operational stage, this is in accordance with the science presented in the animated film Riko The series which is aligned with everyday events or when the characters in the film play.